Efficient charge separation and visible-light response of two-dimensional Janus group-III monochalcogenide multilayers. Issue 2 (19th November 2020) - Bai, Yujie; Guan, Rongfeng; Zhang, Haiyang; Zhang, Qinfang; Xu, Ning
Abstract : The Janus group-III monochalcogenide multilayers with enhanced built-in electric field exhibit excellent performance in harvesting sunlight and efficient separation of electron–hole pairs. Abstract : For realizing high-efficiency solar-to-hydrogen energy conversion via water splitting, great efforts have been made to explore photocatalysts with the ability to harvest sunlight and perform the efficient separation of electron–hole pairs. Two-dimensional (2D) semiconductors with a built-in electric field serve as potential catalysts in this regard. Here, using first-principles calculations, we predict the potential feasibility of 2D Janus group-III monochalcogenide multilayers for use in photocatalytic water splitting. Due to their internal electric field, these multilayer systems have type-II band alignment, facilitating the separation of photogenerated electrons and holes in the different layers. Meanwhile, upon increasing the number of layers, the band gaps of these Janus multilayers decrease, while the band edge positions do not shift significantly due to the built-in electric field, ensuring that these Janus multilayers have suitable band edge positions and enhanced optical absorption coefficients spanning the near-infrared to ultraviolet range for overall water splitting. Furthermore, the intrinsic electric field and small band gap also contribute to a high solar-to-hydrogen (STH) efficiency. The theoretically predicted STH efficiencies are almost larger than 10%, and, additionally, some of them are more than 30%. These results demonstrate that these Janus group-III monochalcogenide multilayers are promising candidate materials to act as ideal photocatalysts for water splitting. Our work also provides a possible approach to modulate the electronic and optical properties of van der Waals (vdW) multilayers for practical applications in electronic and optoelectronic devices.